25 CRS with hipec in advanced epithelial ovarian cancer with comparison of oncological outcome only with CRS + intravenous chemotherapy and CRS plus normothermic intra-peritoneal chemotherapy. (18th September 2019) - Somashekar, S; Rohit Kumar, C; Ashwin, K; Zaveri, S; Ahuja, VK; Rauthan, A; Ramya, Y
Abstract : Objectives: Current standard of care for patients with stage IIIc epithelial ovarian cancer (EOC) is cytoreduction and intravenous (IV) chemotherapy. Intraperitoneal (IP) chemotherapy is considered superior to standard IV chemotherapy. Recent randomised study has shown benefit of cytoreductive surgery (CRS)+ hyperthermic intra-peritoneal chemotherapy (HIPEC) over IV chemotherapy. Methods: 130 patients diagnosed of stage IIIc EOC between 2013–2018 underwent extensive CRS+HIPEC. CRS+IV or CRS+IP was also done during the same period for other patients diagnosed of stage IIIC EOC. Overall details of HIPEC group is reported with comparison of only the oncological outcome of CRS & IV group & CRS+IP group. Results: Of 130 patients, 65.3% & 34.7% had primary and secondary cytoreduction plus HIPEC respectively. Mean PCI was 14.1, duration of surgery 9.41hours & hospital stay 13 days. Multivisceral resection, diaphragmatic resection & bowel resection was required in 12.7%, 50% & 41.8% respectively. Overall G3- G5 morbidity 40% & 30 day mortality 3.6%. With a median follow up of 46 months DFS was 33 & 16 months and OS was not achieved in primary and the recurrent setting respectively. In Comparison CRS with IV group had a DFS & OS of 28 & 42 months whereas CRS with IP group showed 38 & 55 months respectively. Intraperitoneal therapy group had lesser overall recurrence compared to IV arm. Conclusions: CRS+IP & CRS+HIPEC group had lesser overall & peritoneal recurrences and better DFS than CRS+IV group. The role of hyperthermia for intraperitoneal chemotherapy in comparison to IP arm needs evaluation with well designed multi-institutional randomised study.